Sweet Corn Phosphorus Uptake from Sandy Soil Amended with Anaerobically-digested Manure. Issue 18 (10th October 2020) - Collins, H.P.; Kimura, E.; Smith, D.R.
ABSTRACT: Anaerobic digester development on dairy, poultry, and swine confined animal feeding operations (CAFOs) reduce manure storage, produce energy and are poised to supply a variety of nutrient-rich materials. Field experiments were conducted in the Columbia Basin of South-Central Washington to evaluate the yield response and phosphorous (P) use efficiency of sweet corn ( Zea mayes convar. saccharata cv. Sheba) to the application of P from anaerobic-digested manures. Treatments consisted of the application of 0, 10, 20, 40 kg P ha −1 from five sources, three from anaerobic digesters (AD); AD-dairy P fine solids; AD centrifuged poultry solids; and AD dairy-derived struvite-P compared to a commercial poultry fertilizer, commercial mono-ammonium phosphate, and a non-amended control. Sweet corn yields were not significantly different among P amendments or rates of application but were different between years and were greater than the No-P treatment in 2014. Phosphorus recovery efficiency defined as that percentage of applied P recovered by sweet corn averaged 138% among treatments receiving 10 kg P ha −1 and declined to 57% for higher rates of poultry materials and the commercial mono-ammonium phosphate (MAP) in 2013 and declined 50% in 2014 due to lower yields. Although yield was not different the uptake of P among treatments was significantly greater than the unfertilized control. The lack of yield differences among rates of P applied indicates that P was not limiting yield and suggests that under these production conditions the application of 10 kg P ha −1 of any of the amendments was sufficient. Abbreviations: AD: anaerobic digestion; ADD: anaerobic-digested dairy manure; ADP: anaerobic digested poultry manure; ADS: anaerobic-digested struvite; DM – dry matter; MAP – mono ammonium phosphate; PBP a commercial poultry fertilizer; PRD: percent P recovery efficiency difference method; PRB: percent P recovery balance method; PUE: Phosphorus use efficiency; AUE – Agronomic utilization efficiency.